Comparison of the Accuracy of Manual and Digital Cephalometric Prediction Methods in Orthognathic Surgical Planning: A Pilot Study - Can Arslan; Ayşe Tuba Altuğ; Tülin Ufuk Toygar Memikoğlu; Elif Merve Arslan; Ensar Başpınar (Galenos Yayinevi, 2018)
Objective:To compare and evaluate the reliability of manual and digital cephalometric prediction methods in orthognathic surgical planningMethods:Ten adults (5 females and 5 males) with skeletal class III malocclusion were included. The mean patient age was 21.97 years. Pre- to postoperative changes were evaluated using paired t-test. Manual surgical predictions made by tracing on acetate paper and digital predictions made using computer software were compared with actual postoperative values using intraclass correlation coefficient and root mean square.Results:Statistically significant changes were observed in SNA, SNB, ANB, U1i-FH, and Nperp-A following bimaxillary orthognathic surgery (p<0.001). Postoperative changes in Co-A and Nperp-Pg were statistically significant (p<0.05). Comparison of manual and digital surgical predictions with actual postoperative values revealed that overbite and overjet showed the lowest agreements. Manual predictions were less accurate for points that were difficult to distinguish (Co and U6). Skeletal predictions were more accurate than dental predictions.Conclusion:Parameters with low reproducibility (Co and U6) decrease the reliability of predictions. Dental predictions were inaccurate in both methods due to the effects of intermaxillary elastics, but both methods yielded similar predictions for skeletal parameters. The impact of applying strong elastics for postoperative intermaxillary fixation should be considered when making surgical predictions.